2010
DOI: 10.1185/03007991003600271
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of pregabalin in the treatment of fibromyalgia from a UK perspective

Abstract: This model found pregabalin 300 mg and 450 mg to be cost effective compared with placebo and, within the limits of available evidence, against duloxetine using standard UK criteria in patients with fibromyalgia experiencing severe pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Amitriptyline, a tricyclic antidepressant, also has undergone traditional study in the treatment of a wide variety of painful conditions, including MPS [22‐36]. Nortriptyline is a second‐generation tricyclic antidepressant with less incidence of adverse effects compared with amitriptyline.…”
Section: Medicationsmentioning
confidence: 99%
“…Amitriptyline, a tricyclic antidepressant, also has undergone traditional study in the treatment of a wide variety of painful conditions, including MPS [22‐36]. Nortriptyline is a second‐generation tricyclic antidepressant with less incidence of adverse effects compared with amitriptyline.…”
Section: Medicationsmentioning
confidence: 99%
“…However, the effectiveness of these interventions showed conflicting results [12, 13]. In the absence of substantial clinical effects, the cost-effectiveness of interventions in FM is disappointing [1416]. The importance of a prompt (and earlier) diagnosis and of immediate (intensive) intervention are increasingly discussed as potential opportunities to prevent the development of persistent pain and long-term dysfunction and therefore might increase effectiveness of interventions [13, 17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted in the UK found that pregabalin was cost-effective to the UK National Health Service where effectiveness was measured with qualityadjusted life years (QALY) based on a patient's utility gain from treatment response. The incremental cost-effectiveness ratio (ICER) in that study was £23,166/QALY for pregabalin 150 mg BID and £22,533/QALY for pregabalin 225 mg BID compared with placebo 53 . In the severe FM population, pregabalin 225 mg BID was also cost-effective compared with duloxetine 60 mg (ICER ¼ £19,224/ QALY) and 120 mg (ICER ¼ £14,096/QALY) and against gabapentin (ICER ¼ £35,737/QALY).…”
Section: Discussionmentioning
confidence: 99%